Spatial memory and the human hippocampus - Shrager, Yael (National Academy of Sciences, 2007)
The hippocampus and adjacent medial temporal lobe structures are known to support declarative memory, but there is not consensus about what memory functions the hippocampus might support that are distinct from the functions of the adjacent cortex. One idea is that the hippocampus is specifically important for allocentric spatial memory, e.g., the hippocampus is especially needed to remember object locations when there is a shift in viewpoint between study and test. We tested this proposal in two experiments. Patients with damage limited to the hippocampus were given memory tests for object locations in a virtual environment. In the first experiment, participants studied locations of a variable number of images (one to five) and tried to remember the image locations from either the same viewpoint as during study (shift of 0°) or a different viewpoint (shift of 55°, 85°, or 140°). In each viewpoint condition (shifts of 0°, 55°, 85°, and 140°), patients performed normally when remembering one or two image locations. Further, performance declined to a similar degree in each viewpoint condition as patients tried to remember increasing numbers of image locations. In the second experiment, participants tried to remember four images after viewpoint shifts of 0°, 55°, 85°, or 140°. Patients were mildly impaired at all conditions (shifts of 0°, 55°, 85°, and 140°), and the impairment was no greater when viewpoint shifted. We conclude that damage to the hippocampus does not selectively impair viewpoint-independent spatial memory. Rather, hippocampal damage impairs memory as the memory load increases.